THE ROLE OF LANGUAGE EXPRESSIONS IN FORMING THE SCIENTIFIC WORLD VIEW OF PRIMARY CLASS STUDENTS - Mukhtori Mohruy Sodirzoda (American Journals Publishing, 2023)
In this article, in the development of thinking of elementary school students, the level of thinking increases by understanding the meaning of certain expressions in the language, and the ways and methods of forming speech components and expanding the worldview of students through these expressions are revealed.
Keywords: Elementary school, thinking, imagination, mnemonic method, phrase, meaning, visual images, concept, method, methodology, language, consciousness, speech, oral speech, written speech.